Contagion effect in cryptocurrency market - Paulo Ferreira; Éder Pereira (Journal of Risk and Financial Management, 2019)
The rapid development of cryptocurrencies has drawn attention to this particular market, with investors trying to understand its behaviour and researchers trying to explain it. The evolution of cryptocurrencies' prices showed a kind of bubble and a crash at the end of 2017. Based on this event, and on the fact that Bitcoin is the most recognized cryptocurrency, we propose to evaluate the contagion effect between Bitcoin and other major cryptocurrencies. Using the Detrended Cross-Correlation Analysis correlation coefficient (ΔρDCCA) and comparing the period after and before the crash, we found evidence of a contagion effect, with this particular market being more integrated now than in the past-something that should be taken into account by current and potential investors.
Keywords: 330; cryptocurrency; contagion effect; detrended cross-correlation analysis; Bitcoin